Quality of Life Among Latino/a Adults: Examining the Serial Mediation of Network Acculturation, Psychological Acculturation, Social Capital, and Helping-Seeking - Adrian J. Archuleta; Stephanie Grace Prost; Mona A. Dajani (Behavioral Sciences)
Latinos/as are the largest ethnic group in the U.S. and are a continuous source of population growth. Therefore, their health and quality of life are important public health concerns. Acculturation is an important determinant of health for Latinos/as. However, few studies examine models identifying determinants of acculturation along with its relationship to other social and health behaviors. The current study uses social network data from a sample of crowdsourced recruited Latinos/as (N = 300) to examine a structural model between network acculturation, psychological acculturation, social capital, help-seeking, and quality of life (QoL). The model posits several paths through which social networks (i.e., network acculturation) relate to acculturation and other model variables. Directly, network acculturation was found to be significantly related to Latino/a enculturation (−0.83, p = 0.002) and White American Acculturation (0.47, p = 0.003). Latino/a enculturation was related to help-seeking (0.21, p = 0.029) and social capital (0.36, p < 0.001), while White American acculturation was only related to social capital (0.35, p = 0.003). Social capital demonstrated a robust relationship with help-seeking (0.48, p = 0.004) and QoL (0.96, p = 0.003). The findings suggest that determinants of acculturation (i.e., network acculturation) are meaningful contributors to psychological acculturation and other variables relating to Latino/as’ QoL.